Eficacia de la ecografía fast en el diagnóstico de trauma abdominal cerrado en el Hospital Belén de Trujillo - Velarde Marín, Armando Nacho (2014)
Determine if FAST echography had efficacy at diagnosis no penetrant abdominal trauma at Belen Trujillo Hospital. Material and methods: Retrospective, observational, diagnosis test study to aplicatein 70 patients. We calculated the sensitivity, specificity, positive and negative predictive to FAST echography had efficacy at diagnosis no penetrant abdominal trauma with hemoperitoneum. We calculated the chi square test. Gold estándar to diagnosis was exploratory laparotomy and clinical evolution. Results: The sensitivity, specificity, positive and negative predictive to FAST echography had efficacy at diagnosis no penetrant abdominal trauma were 90%, 89%, 98% y 58% respectively. Conclusions: FAST echography had efficacy at diagnosis to no penetrant abdominal trauma with hemoperitoneum